2010
DOI: 10.1094/pdis-06-10-0445
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Eastern Filbert Blight on Corylus avellana ‘Gasaway’ and ‘VR20-11’ Caused by Anisogramma anomala in New Jersey

Abstract: Eastern filbert blight (EFB) is a serious disease of European hazelnut, Corylus avellana L., which causes economic losses in Oregon (OR) where 99% of the U.S. crop is produced. The causal organism, Anisogramma anomala (Peck) E. Müller, is native east of the Rocky Mountains where it is found in association with C. americana Marshall. While C. americana is tolerant, EFB causes cankering, branch dieback, and death of C. avellana (3). EFB was first discovered in Washington State in the late 1960s (1). Since then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The OSU hazelnut breeding program has used 'Gasaway' resistance extensively in breeding, and most recently released cultivars and pollenizers, and advanced selections in trials carry resistance from 'Gasaway'. However, Molnar et al (2010b) showed that an isolate from Michigan can infect 'Gasaway', prompting greater concern about potential breakdown of resistance and a continued search for new resistance sources. Eventually, we envision the pyramiding of two or more resistance genes in a single cultivar for durable resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OSU hazelnut breeding program has used 'Gasaway' resistance extensively in breeding, and most recently released cultivars and pollenizers, and advanced selections in trials carry resistance from 'Gasaway'. However, Molnar et al (2010b) showed that an isolate from Michigan can infect 'Gasaway', prompting greater concern about potential breakdown of resistance and a continued search for new resistance sources. Eventually, we envision the pyramiding of two or more resistance genes in a single cultivar for durable resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The potential breakdown of single resistance genes is always a concern in disease resistance breeding. Molnar et al (2010aMolnar et al ( , 2010b showed that an isolate from Michigan was able to infect 'Gasaway' and OSU 408.040 in New Jersey. One strategy for durable resistance is the pyramiding of two or more resistance genes in a single cultivar.…”
mentioning
confidence: 99%
“…EFB is generally more severe in a field nursery in New Jersey than in Oregon. In New Jersey, 'Gasaway' trees showed a few small cankers on small twigs (Molnar et al, 2010b). The cankers have stromata, and the cankers expand slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Most resistant selections from the breeding program carry 'Gasaway' resistance. In greenhouse inoculation studies with various isolates of A. anomala, Molnar et al (2010aMolnar et al ( , 2010b demonstrated that an isolate from Michigan was able to infect 'Gasaway', emphasizing the importance of using more than one source of resistance in breeding. Greenhouse inoculation studies (Chen et al, 2007;Coyne et al, 1998;Lunde et al, 2000;Sathuvalli et al, 2010) identified several C. avellana selections resistant to EFB.…”
mentioning
confidence: 99%
“…Alternaria from several distinct species can also cause diseases on hazelnut (Belisario et al 2004). In North America, the main diseases of hazelnut are caused by Anisogramma anomala (Molnar et al 2010), with cankering, branch dieback and tree death seen.…”
Section: Introductionmentioning
confidence: 99%